Features of spoken language dialogue in the language of youth (Eurasian Journal of Philology Science and Education, 2021)
The article says that spoken language is not only spoken in real life, but also has its own generalized structural state. In the artistic structure, spoken language changes differently. The pronunciation of spoken language and its use in written language are not the same. Thought in written language is characterized by style, it is systematized with the necessary words and expressed one-sided, in a spoken language, it is suitable for listeners, deviates from the written language model, the difference of speech from written language is explained by examples in the article. It is argued that literary works are directed to the spoken language through dialogues. Although they have their own specific differences, some artistic languages take their place in the stylistic sequence of everyday spoken speech through their dialogues. Despite its specific differences, some works of art occupy a stylistic range of everyday spoken language through dialogues. The relevance of the research work is related to the recognition of the features of the Kazakh dialogue, its communicative aspect. On this basis, dialogues of young people in artistic works and colloquial speech are taken, communicative and pragmatic features are analyzed.In addition, the article also identifies the features and purpose of oral dialogue in the language of youth. The pragmatics and stylistic features of dialogues in the spoken language of youth aged 16-30, the phenomenon of saving language units used in dialogue are also substantiated and explained by examples from the language of youth.